Desain Pembelajaran Digital Berbasis Blended Learning dalam Meningkatkan Kemandirian Belajar Siswa - Rahman, David; Hdayat, Samsul; Gusmaneli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The rapid development of digital technology has significantly influenced the field of education, particularly in how teachers design and implement learning processes. One of the most relevant approaches in the modern era is blended learning, a combination of online and face-to-face learning designed to create a more flexible and meaningful learning experience. The digital instructional design based on blended learning aims to provide opportunities for students to learn independently through access to digital learning resources while still receiving direct guidance from teachers. This approach is believed to enhance students’ learning autonomy, responsibility, and ability to manage their time and learning strategies effectively. By utilizing digital technology, students can adjust their learning styles according to their individual needs and pace, enabling them to take a more active role in knowledge exploration. Previous studies have shown that blended learning implementation can improve students’ learning motivation, participation, and critical thinking skills. Therefore, digital learning design based on blended learning serves as an innovative strategy to realize adaptive and student-centered 21st-century education.